On reliable collaborative mobility services - F. G. Osório, A. Luís (2018)
Current approaches for development of collaborative business process automation, when requiring the participation of multiple stakeholders, lack proper formalization in terms of the required informatics systems landscape. Existing solutions depend on specific technology strategies and do not offer a suitable model for the fast-growing collaborative services. In this paper, we present the concept of an open informatics system of systems (ISoS), as a holistic framework that can be applied to a European wide payment system for collaborative multimodal mobility services. To illustrate how the ISoS framework could be applied in practice, we consider the payment service to support public transports, motorway and bridges tolling, payment in parking lots, bicycle renting and payment in a fueling station, all under a single contract. While each participating organization (any infrastructure operator) is free to adopt any applicable technology, the proposed ECoNet collaboration infrastructure is aimed to support a multi-supplier (open) informatics system technology landscape. Based on results from previous research, the paper introduces a strategy to allow effective and reliable EU wide collaborative mobility services.